Effects of Different Exercise Training Protocols on Gene Expression of Rac1 and PAK1 in Healthy Rat Fast- and Slow-Type Muscles - Laine, Saara; Högel, Heidi; Ishizu, Tamiko; Toivanen, Jussi; Yli-Karjanmaa, Minna; Grönroos, Tove J.; Rantala, Juha; Mäkelä, Rami; Hannukainen, Jarna C.; Kalliokoski, Kari K.; Heinonen, Ilkka (Frontiers in Physiology, 2020)
Purpose: Rac1 and its downstream target PAK1 are novel regulators of insulin and exercise induced glucose uptake in skeletal muscle. However, it is not yet understood how different training intensities affect the expression of these proteins. Therefore, we studied the effects of high-intensity interval training (HIIT) and moderate intensity continuous training (MICT) on Rac1 and PAK1 expression in fast-type (gastrocnemius, GC) and slow-type (soleus, SOL) muscles in rats after HIIT and MICT swimming exercises. Methods: The mRNA expression was determined using qPCR and protein expression levels with reverse-phase protein microarray (RPPA). Results: HIIT significantly decreased Rac1 mRNA expression in GC compared to MICT (p=0.003) and to the control group (CON) (p=0.001). At the protein level Rac1 was increased in GC in both training groups but only the difference between HIIT and CON was significant (p=0.02). HIIT caused significant decrease of PAK1 mRNA expression in GC compared to MICT (p=0.007) and to CON (p=0.001). At the protein level, HIIT increased PAK1 expression in GC compared to MICT and CON (by 17%), but the difference was not statistically significant (p=0.3, p=0.2, respectively). There were no significant differences in the Rac1 or PAK1 expression in SOL between the groups. Conclusion: Our results indicate that HIIT, but not MICT decrease Rac1 and PAK1 mRNA expression and increase the protein expression of especially Rac1, but only in fast-type muscle. These exercise training findings may reveal new therapeutic targets to treat patients with metabolic diseases.